Design implications of IS 456: 2000 for high performance concrete - Khadiranaikar, R.B.; Awati, M. M. (Journal of Structural Engineering, 2024)
IS 456 (1978) was formally introduced the limit state design of reinforced concrete. Some of the important changes incorporated in fourth edition of IS 456 (2000) are, the aspect of durability and revision of formula for estimation of modulus of elasticity in section 1.Requirements for fire resistance and regulations for deflections in flexural members in section 3. However, no recommendations are made for use of high performance concrete for flexural members in the new code. In view of this, the present experimental study is taken up to develop the stress-block parameters for high performance concrete. New parameters are proposed based on tests on three series of specimens such as fixed neutral axis specimens, eccentrically loaded columns and tests on beams for strength of concrete in the range of 40 to 120 MPa with respect to cylinder and cube strength of concrete. The experimental data of 14 columns in flexure is compared with the interaction curves developed using the proposed stress-block parameters.